Pergeseran Paradigma Pemasyarakatan: Implementasi Pembinaan Kemandirian Narapidana Berdasarkan Undang-Undang Pemasyarakatan - Nazhifah Nazhifah; Muhammad Darwis; Kairuddin Kairuddin; Dian Anggreni Thamrin (Jurnal Litigasi Amsir, 2026)
This study analyzes the implementation of the correctional system at Class I Correctional Institution Makassar following the enactment of Law Number 22 of 2022 on Corrections, which shifts the paradigm from a punitive approach to a more humanistic, rehabilitative, and restorative one. The research employs a normative-empirical method that combines legislative and conceptual approaches with field observations and interviews involving officers, heads of divisions, and inmates. The findings show that rehabilitation programs are carried out through personality development, economic self-reliance, and social reintegration, implemented via intramural activities and internal–external assimilation, and supported by collaboration with universities, government agencies, and private sector partners. These programs not only strengthen inmates’ moral awareness but also equip them with vocational skills and work experience to enhance their post-release employability and reduce recidivism. However, the implementation still faces significant challenges, including overcrowding, diverse inmate backgrounds, limited motivation, budget constraints, marketing difficulties for inmate-produced goods, and complex administrative procedures for external activities. The study concludes that, despite these obstacles, the correctional system at Class I Correctional Institution Makassar has substantively realized the spirit of Law Number 22 of 2022, while requiring continuous policy support, expanded stakeholder collaboration, and more flexible governance to optimize humane and effective rehabilitation.